Language attitudes in a group of Cubans during migratory journey and establishment in Mexico - Larios Loza, Brenda B. (Verbum – Analecta Neolatina, 2024)
The current article explores the linguistic attitudes of thirteen Cuban migrants residing temporarily in migrants’ shelters in Mexico. This case study aims to demonstrate their posture towards the change in language variety and lexicon as they integrate into Mexican society. It sought to examine their positive and negative affective attitudes towards Mexican Spanish through a semi structured questionnaire and qualitative analysis of recorded interviews. The findings reveal similarities and differences in the Cubans’ desire to maintain or change their Spanish variety, highlighting the influence of migratory more than the social factors on their language decisions.